Synthesis of multi-shelled ZnO hollow microspheres and their improved photocatalytic activity - Zeng, Xiangyun (Springer, 2014)
Herein, we report an effective, facile, and low-cost route for preparing ZnO hollow microspheres with a controlled number of shells composed of small ZnO nanoparticles. The formation mechanism of multiple-shelled structures was investigated in detail. The number of shells is manipulated by using different diameters of carbonaceous microspheres. The products were characterized by X-ray powder diffraction, scanning electron microscopy, and transmission electron microscopy. The as-prepared ZnO hollow microspheres and ZnO nanoparticles were then used to study the degradation of methyl orange (MO) dye under ultraviolet (UV) light irradiation, and the triple-shelled ZnO hollow microspheres exhibit the best photocatalytic activity. This work is helpful to develop ZnO-based photocatalysts with high photocatalytic performance in addressing environmental protection issues, and it is also anticipated to other multiple-shelled metal oxide hollow microsphere structures.